Longitudinal Study of the Relationship among Craniocervical Morphology, Clinical Progression, and Syringomyelia in a Cohort of Cavalier King Charles Spaniels. (17th June 2016) - Cerda‐Gonzalez, S.; Olby, N.J.; Griffith, E.H.
Abstract : Background: Craniocervical junction (CCJ) anomalies and secondary syringomyelia are commonly diagnosed in Cavalier King Charles spaniel (CKCS). Familiarity with the natural history of these abnormalities is vital to understanding the disease syndrome. Objective: To evaluate magnetic resonance imaging (MRI) predictors of worsening clinical signs, syringomyelia, and morphology in CKCS longitudinally. Animals: Fifty‐four client‐owned CKCS, 5–13 years old; 50% currently symptomatic. Methods: Longitudinal observational study. We enrolled CKCS with an MRI of the CCJ performed ≥3 years earlier. We used questionnaires and neurologic examinations to grade initial and current clinical status. Dogs that could be anesthetized were reimaged. Morphologic assessments included the presence and severity of: Chiari‐like malformations, medullary position, atlantooccipital overlapping (AOO), dorsal atlantoaxial bands, and syringomyelia. Cranial cavity volumes and foramen magnum height were measured. Results: Clinical status was evaluated in 54 dogs; 36/54 were reimaged. Mean follow‐up was 71 months. Of initially asymptomatic dogs, 32% were symptomatic at re‐evaluation. Of initially symptomatic dogs, 56% had worsened; 13% had improved with medical management. The morphology of the CCJ at initial imaging did not predict development of either new or worsened signs or syringomyelia by the time of re‐evaluation. Conclusion: Craniocervical junction anomalies assessed in this study did not appear predictive of future clinical status or syringomyelia in our cohort. The impacts of syringomyelia, AOO, and atlantoaxial bands on future clinical status merit further study in larger groups of CKCS. Clinical progression in our cohort of medically managed CKCS did not differ substantially from published reports of those treated surgically.